PELUANG ENTERPRENEUR WANITA TANI DALAM DIVERSIFIKASI UBI KAYU SEBAGAI BAHAN BAKU PANGAN KONVENSIONAL - Safrin Edy; Wa Ode Al Zarliani; La Ode Muhammad Mustari; Wa Ode Siti Hamsiar; Sufilawati Sufilawati; Muhammad Nur Amin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The purpose of this community service activity is to carry out counseling and empowerment in the process of processing cassava into kaopi (flour) which has a soft texture, white color and a distinctive aroma (like fresh cassava) and a good packaging system and branding for business groups. women farmers in Bola Village, Batauga District, South Buton Regency, Southeast Sulawesi Province. The method of implementing community service is through the participatory action research (PAR) method which is carried out using participatory techniques such as Focus Group Discussions (FGD), surveys with the involvement of all members of business groups as interviewers, formal and non-formal discussions and discussions with stakeholders, so that people recognize the potential and existing problems and encourage participation in the activities carried out. The results of the implementation of community service activities show that the process of processing cassava into good and soft kaopi has been successful because the women farming business group has understood the stages in the kaopi processing process. So that the resulting kaopi has a soft texture, white color, does not smell and has been packaged properly in branded packaging.